Climate action assessment in three small municipalities in British Columbia: advancements vis-à-vis major neighboring cities - François Jost, PhD; Ann Dale, PhD; Robert Newell, PhD; John Robinson, PhD (Current Research in Environmental Sustainability, 2020)
This paper applied a recently developed Local Government Climate Action Assessment Framework to identify whether small municipalities in British Columbia are on track to meet their climate targets and to better understand the effectiveness of their climate-related actions. The aim of this paper was (1) to further test the assessment framework by evaluating its applicability for smaller municipalities, (2) to evaluate and categorize local progress in three small cities, namely Campbell River, Prince George and Revelstoke, and (3) to contrast these climate actions with actions taken by larger municipalities in BC, using the same assessment framework. This assessment revealed that key external support made available to expand on their Integrated Community Sustainability Plans provided for striking similarities among the three case studies regarding their strategies and plan formulations for which actions were largely transformative or reformative. However, the three small cities were lacking periodic reporting and monitoring of actions and presented shorter timeframes of up to 20-50 years for their planning horizons, all of which negatively impact their prioritization strategies. The main difference between larger and smaller cities was found among actions related to the feedback and evaluation category of the framework, with smaller cities performing more poorly. Greater shift in priorities away from climate change-related actions were evident in smaller local governments, signalling their more vulnerable position regarding changes in leadership in local and provincial administrations. This study highlights the key role that strategic alliances, networks, and external champions as partners play in planning and implementing climate action and in increasing public interest in sustainability. Thus, these should be fostered and promoted to keep building local capacity and effectively accelerate greater change through e.g., strengthening their capacity to implement, monitor and evaluate climate actions.